PELAKSANAAN PROGRAM DINIYAH DALAM MEMBENTUK KARAKTER RELIGIUS - Malihatun Mukaromah; Sa’idy Sa’idy; Baharudin Baharudin; Riyan Terna Kuswanto (Ilmuna: Jurnal Studi Pendidikan Agama Islam, 2025)
This study aims to analyze the implementation of the diniyah program in shaping religious character, determine the role of madrasah and diniyah teachers in shaping religious character, and the impact of the implementation of the diniyah program in shaping character at MTs Miftahul Huda Ma'arif 23 Central Lampung. This research uses descriptive research which includes qualitative research. Data collection techniques by means of semi-structured interviews, non-participant observation and documentation. Sample determination using purposive sampling technique. Data analysis was carried out by reducing data, presenting data and drawing conclusions. The data validity test is by triangulating sources, techniques and time. The results showed that the implementation of the diniyah program in shaping religious character consisting of activities of reading prayers and asmaul husna, reading the Qur'an, learning tajweed science, tahfidz Qur'an, practicing ablution and prayer had a positive impact on the religious character of students who were getting better and disciplined in terms of carrying out worship such as prayer, the ability to read the Qur'an which is increasingly fluent and has memorized the Qur'an, likes to read the Qur'an, has a polite attitude to the teacher, does not skip class during class hours, shows respect for differences in the implementation of worship, has a sense of empathy for friends who are in trouble, leaving school always ablution, not ashamed to say sorry if you do wrong.